Contrasting immune responses in COVID-19: insights from healthcare workers and infected patients on plasmablast, pDC, and NK cell dynamics - Martín-Pedraza, Laura; Rodríguez-Martín, Eulalia; De La Torre-Tarazona, Erick; Moreno, Elena; Pariente-Rodríguez, Roberto; Walo-Delgado, Paulette Esperanza; García-Pérez, Javier; Díaz, Jorge; Luna, Laura; Rodríguez-Dominguez, Mario; Galán, Juan Carlos; Geraldine Rita, Claudia; et al. (Frontiers in Immunology, 2026)
BackgroundThe COVID-19 pandemic, caused by SARS-CoV-2, has highlighted significant variability in disease severity, ranging from asymptomatic cases to severe acute respiratory distress syndrome.ObjectiveUnderstanding the immune responses that contribute to this variability, particularly among healthcare workers (HCWs) frequently exposed to the virus, is essential.Materials and methodsThis was a prospective single-center longitudinal cohort study. We included hospitalized COVID-19+ patients, classified as having mild or moderate-to-severe symptoms, and unvaccinated HCWs with low susceptibility. Peripheral blood mononuclear cells (PBMCs) were collected and analyzed using flow cytometry. We measured the frequencies of key immune subsets, including plasmablasts, plasmacytoid dendritic cells (pDCs), and Natural Killer (NK) cells. SARS-CoV-2 neutralizing antibodies (NAbs) were quantified using pseudotyped HIV particles.ResultsCOVID-19+ patients exhibited a significant increase in plasmablasts, a B-cell subset responsible for producing neutralizing antibodies, which correlated with disease severity (p=0.0082). Conversely, uninfected HCWs had low levels of plasmablasts but significantly higher levels of plasmacytoid dendritic cells (pDCs) (p<0.0001), which produce interferons upon activation by viral antigens. Additionally, HCWs had a higher percentage of CD56bright NK cells than the susceptible patients (p=0.02).ConclusionOur findings suggest that immune dysregulation, characterized by increased plasmablasts and reduced pDC and NK cell responses, contributes to COVID-19 severity. Strong pDC and NK cell responses may confer protection against SARS-CoV-2. These insights into immune responses may inform strategies for therapeutic interventions and vaccine development.